Cultural studies and the methodological revolution from specialization to interdisciplinarity and compound thinking - Rezgui, Abdelkrim; Boulkandoul, Fouzia (Journal of Human Sciences, 2023)
The cultural studies are considered to be one of the most fertile knowledge fields that appeared after the post modernity era. This came as a reaction against the textual critical practices as an activity based on interdisciplinarity. Basing on that idea, our main focus in this research paper is on the clarification of the concept of cultural studies and its relation with the interdisciplinary studies and those post specialization. In addition, we will try to discover the relation between cultural studies and the compound thinking of Idgar Mouran.